Diagnosing FSGS without kidney biopsy – a novel INF2-mutation in a family with ESRD of unknown origin. Issue 1 (December 2016) - Münch, Johannes; Grohmann, Maik; Lindner, Tom; Bergmann, Carsten; Halbritter, Jan
Abstract Background Patients on renal replacement therapy are often unaware of their underlying condition and hence suffer from so-called end-stage renal disease (ESRD) of unknown origin. However, an exact diagnosis is not only important for better estimating the prognosis, but also when preparing for kidney transplantation. Whilst patients with FSGS without a confirmed genetic cause have a high recurrence rate in the transplanted organ, patients with a mutation generally exhibit no recurrence and have a good prognosis. Furthermore, renal biopsy, which may be helpful for differential diagnosis, is usually contraindicated in end-stage kidneys. We here present the case of familial ESRD of unknown origin, which could be resolved by targeted genetic testing prior to planning of kidney transplantation. Case presentation A 32-year-old female with ESRD and nephrotic range proteinuria was admitted to our clinic. Family-history revealed that both mother and maternal grandmother had ESRD of unknown origin. As renal biopsy was impossible due to atrophic kidneys, we performed mutation analysis of genes known for dominant forms of FSGS and found a novel heterozygous mutation ofINF2 (c.485 T > C, p.Leu162Pro). The same mutation could be detected in the index patient's mother (ESRD at age 50) and three brothers with normal serum-creatinine but mid or low range proteinuria. Conclusions Genetic testing is warranted in families with ESRD of unknown origin and may provide a robust diagnosis even without kidney biopsy. It will help detecting relatives at risk who have to be excluded from potential kidney donation and who may benefit from timely initiation of protective measures in order to slow down disease progression.